(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines the issue of the state and development of sports facilities in the Kirovohrad region in the conditions of a full-scale war. The purpose of the study is to analyze the dynamics of quantitative and qualitative indicators of sports facilities in the Kirovohrad region from 2021 to 2024. A set of methods was applied: theoretical analysis and generalization of data from scientific and methodological literature and Internet resources; analysis of statistical reporting documents in forms No. 5–FK and No. 2–FK of the Department of Youth and Sports of the Kirovohrad Regional Military Administration from 2021 to 2024; pedagogical experiment and methods of mathematical statistics. It was established that as of 2024, 3,101 separate sports facilities are operating in the Kirovohrad region. The largest number of facilities is in municipal ownership (2,501 units) and is located in educational institutions (1,984 units). Flat sports facilities (1,747 units) have become widespread: sports grounds, football fields, sports grounds with training equipment, multi-purpose courts, tennis courts, etc. Among indoor sports facilities, the largest number of sports halls with an area of at least 165 m² was found. There are 135 sports facilities adapted for people with disabilities. Only one facility has been newly built and 78 are not operating. A decrease in the number of sports facilities by 0.06% was detected in the Kirovohrad region from 2021 to 2024. At the same time, an increase in the number of state-owned sports facilities by 9.52% and municipal ones by 1.79% was detected. The number of privately owned facilities decreased by 9.61%. An increase in the number of non-operating facilities by 59.18% and a decrease in the number of newly built facilities by 90.91% were detected.